Evaluation of plant extracts, fungicides, bio-agent and soil amendments against foot and root rot disease of betelvine caused by Sclerotium rolfsii under field condition - Rahman, MH; Islam, MR; Aminuzzaman, FM; Latif, A; Nahar, S (Bangladesh Journal of Agricultural Research, 2020)
The studies were carried out on the management of foot and root rot disease caused by Sclerotium rolfsii Sacc. of betelvine (Piper betle L.) during April, 2017 to April, 2018 in a betelvine orchard (baroj) in the experimental farm of Sher-e-Bangla Agricultural University, Dhaka. There were 10 treatments, namely Provax 200, Tilt 250 EC, Score 250 EC, Pencozeb 80 WP, Garlic clove extract, Allamanda leaf extract, Poultry waste, Vermi-compost, Trichoderma harzianum and Control. The in-vivo evatuation, plant was inoculated by S. rolfsii after six month of plantation. The evaluation revealed that the lowest disease incidence of 8.33% was found in Provax 200 whereas the highest disease incidence of 91.67 was recorded under the untreated control treatment. The maximum of 90.91% reduction in disease incidence over control was found under Provax 200, which was significantly higher compared to all other treatments. Among the treatments, Provax 200 was noted as the most effective fungicide followed by Score 250 EC. The highest yield (7.57 t/ha) at 120 days after inoculation was found in case of Provax 200 which was 330.1% increased over untreated control. Stem and soil treated with Provax 200 including spraying at 3 days after inoculation, then sprayed at 7 days’ intervals minimized disease incidence and increased yield. Among the eco-friendly approach, Garlic clove extract, Trichoderma harzianum and soil amended with Vermi-compost also showed better performance in controlling foot and root rot disease of betelvine as compared to control. Bangladesh J. Agril. Res. 44(4): 669-677, December 2019